Women empowerment initiatives under the Farmer FIRST programme for the livelihood development of tribal farm women in Chhattisgarh - Mooventhan, P.; Verma, Hem Prakash; Singh, Suman (Indian Farming, 2025)
The Farmer FIRST Programme (FFP), implemented by ICAR-NIBSM, Raipur, aimed to enhance the livelihoods and empowerment of tribal farm women in Chhattisgarh through diversified agricultural enterprises. The project was undertaken in five tribal villages, namely Bakla, Kharaha, Bamhani, Kurraha, and Kharri of Kasdol block in Baloda Bazar district. Five key interventions were introduced: mushroom production, nutritional home gardens, agro-processing centres, goat farming, and Kadaknath poultry farming. These initiatives provided farm women with training, resources, and technology for skill development and income generation. Mushroom production benefitted three SHGs and 30 farm families, generating an annual income of `1,44,000; nutritional home gardens improved family nutrition and saved over `2,400 per household annually; agro-processing centres supported 152 farm families with an annual income of `4,78,200; goat farming engaged 83 women and generated a net income of `3,95,270; and Kadaknath poultry farming benefitted 20 women with an income of `2,10,000. Overall, more than 485 farm women were empowered, collectively earning over `12,29,870 annually. The FFP interventions effectively promoted economic independence, entrepreneurship, and sustainable livelihood opportunities among tribal farm women, contributing to their social and economic empowerment.